Goldie Socks and the three libearians - Hopkins, Jackie. (Upstart Books, 2007)
A humorous adaptation of the folktale Goldilocks and the three bears, which portrays the bears as "libearians" and Goldie Socks finds just the right book and the perfect place to read it.